Mosaic trisomy 18 at amniocentesis associated with a favorable fetal outcome in a pregnancy - Chih-Ping Chen; Te-Yao Hsu; Ching-Chang Tsai; Schu-Rern Chern; Shin-Wen Chen; Fang-Tzu Wu; Peih-Shan Wu; Chen-Chi Lee; Li-Feng Chen; Chen-Wen Pan; Wayseen Wang (Elsevier, 2022)
Objective: We present prenatal diagnosis of mosaic trisomy 18 by amniocentesis associated with a favorable fetal outcome in a pregnancy. Case report: A 42-year-old, gravida 4, para 2, woman underwent amniocentesis at 18 weeks of gestation because advanced maternal age. Amniocentesis revealed a karyotype of 47,XX,+18[6]/46,XX[17]. Simultaneous array comparative genomic hybridization (aCGH) on uncultured amniocytes showed the result of 45% mosaicism for trisomy 18. At 25 weeks of gestation, the woman underwent repeat amniocentesis which revealed a karyotype of 47,XX,+18[10]/46,XX[24]. Simultaneous aCGH on uncultured amniocytes showed the result of arr 18p11.32q23 (148,963-78,012,829) × 2.3 [GRCh (hg19)] with a log2 ratio of 0.2-0.25 compatible with 30-38% mosaicism for trisomy 18. The parental karyotypes were normal. Prenatal ultrasound was unremarkable. Interphase fluorescence in situ hybridization (FISH) on uncultured amniocytes showed 27% (27/100 cells) mosaicism for trisomy 18. Quantitative fluorescent polymerase chain reaction (QF-PCR) on uncultured amniocytes excluded uniparental disomy (UPD) 18. Non-invasive prenatal testing (NIPT) analysis at 34 weeks of gestation revealed a significant gene dosage increase of chromosome 18 (29.95; normal control: −3.0-3.0). At 39 weeks of gestation, a 2840-g phenotypically normal baby was delivered. The cord blood had a karyotype of 47,XX,+18[8]/46,XX[32]. The placenta was trisomy 18 of maternal origin. The umbilical cord had a karyotype of 47,XX,+18[2]/46,XX[38]. At age 1½ months, the peripheral blood had a karyotype of 47,XX,+18[5]/46,XX[35], and FISH analysis on buccal mucosal cells revealed 2% (2/102 cells) mosaicism for trisomy 18. When follow-up at age seven months, the neonate was phenotypically normal, and the peripheral blood had a karyotype of 47,XX,+18[1]/46,XX[39]. Conclusions: Mosaic trisomy 18 at amniocentesis without abnormal fetal ultrasound can be associated with a favorable outcome, and the abnormal trisomy 18 cell line may decrease progressively after birth.